Study of States and Characteristcis of the Soul in the Station of Imagination and its Consequences for the Transcendent Philosophy - behzad mortezai (حکمت و فلسفه, 2012)
In the history of Islamic Philosophy, since Farabi's time to the present, the faculty of imagination and imaginary forms have been among so important issues that some scholars have claimed that this is one of the distinct features of the Islamic philosophy. Farabi has explained his theory of prophecy based on the imaginal world. Ibn Sina, Suhrawardi, Mulla Sadra, and their followers succeeded to reconcile religion and philosophy, intuition and argumentation, transmitted sciences and reason based on the idea of imaginal world. The main issue discussed in the present article is states of the soul in the station of imagination; and the most important issue discussed here is arguments posed to prove immateriality of the soul which is of paramount importance in "knowledge of the soul" and is regarded as an important development in philosophical "knowledge of the soul". When immateriality of the soul in the station of imagination is somehow proved, it will be proved that, in spite of views posed by the Peripatetics and Illuminationists, man is not a two-dimensional being (consisted of body and reason); but rather, he enjoys three dimensions and three existential modes: material and corporal mode, formal and purgatorial mode, and rational mode. For the latter, Mulla Sadra has posed many arguments and, as he stipulates, he is the first one in the history of philosophy who has proved some immateriality and independence from body for the faculty of imagination. These arguments are studied and discussed in the present article.